Trauma-Induced Damage-Associated Molecular Patterns-Mediated Remote Organ Injury and Immunosuppression in the Acutely Ill Patient - Vourc’h, Mickael; Roquilly, Antoine; Asehnoune, Karim (Frontiers in Immunology, 2018)
Trauma is one of the leading causes of death and disability in the world. Multiple trauma or isolated traumatic brain injury are both indicative of human tissue damage. In the early phase after trauma, damage-associated molecular patterns (DAMPs) are released and give rise to sterile systemic inflammatory response syndrome and organ failure. Later, DAMPs protracted inflammation following sepsis will favor hospital-acquired infection and will worsen patient's outcome through immunosuppression. Throughout medical care, ICU, or surgical procedures, severe trauma patients will be subjected to endogenous or exogenous DAMPs. In this review, we summarize the current knowledge regarding DAMP-mediated SIRS or IS and the clinical consequences in terms of organ failure and infections.